コウゾウ タンサ ヨウ ジシン ハケイ シュウロク ソウチ ノ ナンキョク ニオケル ドウサ トクセイ - 田中, 俊行; タナカ, トシユキ; 金尾, 政紀; カナオ, マサキ; Tanaka, Toshiyuki; Kanao, Masaki (1996)
P(論文) 第36次日本南極地域観測隊地球物理定常部門は, 地震波形収録用データロガー(白山工業LS-8000VF, LS-8000SH)を用いた自然地震観測を昭和基地周辺で行った。本観測は南極の自然条件下でのこれらのロガーの基本的動作性能を調べることを目的としている。数回の野外観測の結果, 厳冬季でも低温対策を施すことによって, 正常に動作することが確認された。しかし, 収録された波形は低温による性能低下により, 電圧オフセットが見られ, 入力換算雑音もカタログ値を越えるものとなった。春季~夏季は観測はおおむね順調で, いくつかの地震波形も記録した。本報告では, 観測方法, 観測波形, ノイズレベルの評価, 発生した故障と動作不良について述べ, 今後の野外観測の指針となることを目的とする。 During the winter season of the 36th Japanese Antarctic Research Expedition (JARE-36; from February 1995 to January 1996), We carried out seismic observations using data loggers (Hakusan Corp. LS-8000VF and LS-8000SH) around Syowa Station (69.0°S, 39.6°E). We did experiments to evaluate the capability of the loggers under meteorological conditions of Antarctica, such as low temperature. It was confirmed, even in the winter season, the loggers operated normally when a heater and blanket were used as protection against the cold. However, high voltage offsets and increasing input noise are seen at temperature below -40℃. In the spring and summer seasons, observations were carried out without any problems so that we could record some seismic waves. This report describes observation methods, observation results, discussions of noise levels, troubles encountered, and plans for future outdoor observations. departmental bulletin paper